COMPARATIVE STUDY OF HEAVY METALS IN PLANT AND SOIL OF SOME SELECTED MEDICINAL PLANT (FUDMA JOURNAL OF SCIENCES, 2020)
Essential heavy metals like Iron, Nickel, Manganese, Zinc, Copper, Cobalt and non-essential like Cadmium, Lead, and Chromium were analyzed in five selected medicinal plants (Newbouldia leaveis, Chromolaena odorata, Chrysophyllum albidum, Azadirachta indica and Morinda lucida) as well as the soil of each medicinal plants for their metal ion concentration using atomic absorption spectrophotometeric method (AAS). The concentration level of heavy metals in the selected plants were found in the order of Fe (829mg/kg) > Mn (531 mg/kg) > Zn (111 mg/kg) > Pb (88 mg/kg) > Cu (36.5 mg/kg) > Co (15 mg/kg) > Ni (15 mg/kg) > Cr (12 mg/kg) > Cd (9mg/kg). The concentrations found in the soil are in the order; Fe (2167.5 mg/kg) > Mn (1380 mg/kg) > Cr (445 mg/kg) > Pb (207 mg/kg) > Ni (197.5 mg/kg) > Co (188.75 mg/kg) > Zn (141.25 mg/kg) > Cu (81.25 mg/kg)> Cd (12.5 mg/kg).  Iron, Cobalt, Cadmium and Nickel were found above the permissible limit in both plant and soil samples. The concentration of Cu (1.0 mg/kg) Pb (1.0 mg/kg) and Cr (0.5 mg/kg) were found to be below the permissible limit in Morinda lucida plant. Other metals below the permissible limits include Zn (12.5 mg/kg) in the plant of Chromolaena odorata and (26.5mg/kg) in Chrysophyllum albidium. Mn was also found to be (113.5mg/kg) in Newbouldia leaveis and (1.0mg/kg) in Morinda lucida plant respectively.
Keywords: essential heavy metals, non-essential heavy metals, medicinal plants, atomic absorption spectroscopy